KONSEP PEMBIAYAAN BERBASIS AKAD JUAL BELI PADA BAITUL MAAL WAT TAMWIL PAHLAWAN TULUNGAGUNG - Ike Nofita Nurohmah; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
Financing using a sale and purchase contract is one of the most dominant financing in Islamic financial institutions. One of the Islamic microfinance institutions namely baitul maal wat tamil has two types of sale and purchase agreements on its financing products, namely the contract of sale and purchase of murabahah and bai bithaman ajil. This study discusses the concept of financing based on the sale and purchase contract, namely murabahah and bai bithaman ajil on baitul maal wat tamwil (BMT) Pahlawan Tulungagung. The things that need to be reviewed in the practice of the ajabahah and bai bithaman contract are adjusted to the points in the DSN-MUI Fatwa on murabahah financing. This study uses qualitative methods with descriptive case study strategies. Data collection through interviews with four respondents consisting of financing managers, managers and two members of the financing of buying and selling financing and documentation. Interpretation and conclusions are made by linking between data obtained in interviews and documentation. The results of the study show that the concept of financing murabahah and bai bithaman ajil in BMT Pahlawan is not fully in accordance with the DSN-MUI Fatwa regarding the purchase of goods. However, this is still tolerated because of the limitations of BMT to purchase goods which then applies the Al-hajatu tunazzilu rule, manzilata al-dharurah, which is a requirement or need to occupy an emergency position so that the purchasing system is allowed.Keywords: Financing, Murabaha, Bai bithaman ajil, DSN-MUI, BMT Pahlawans